Dendritic flux avalanches in a superconducting MgB2 tape. (1st November 2017) - Qureishy, T; Laliena, C; Martínez, E; Qviller, A J; Vestgården, J I; Johansen, T H; Navarro, R; Mikheenko, P
Abstract: Tapes of MgB2 with high critical current have a significant technological potential, but can experience operational breakdown due to thermomagnetic instabilities. Such events are routinely registered by magnetisation measurements, but were never observed by direct imaging techniques. Here we report magneto-optical imaging visualisation of a tape with reduced thickness and enhanced critical current density. The spatial structure of the thermomagnetic avalanche events was resolved, and the reproducibility and nucleation thresholds were determined. Avalanches appearing at low fields are small intrusions at the tape edges, while larger fields create more extensive avalanches having dendritic structures similar to those observed in thin-film superconductors. In contrast to dendritic avalanches in thin films, the avalanches in the tapes show reproducibility to a larger extent.